If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4+1/3y=-5
We simplify the equation to the form, which is simple to understand
4+1/3y=-5
We move all terms containing y to the left and all other terms to the right.
+3y=-5-4
We simplify left and right side of the equation.
+3y=-9
We divide both sides of the equation by 3 to get y.
y=-3
| -3/2x-9=6 | | u/9=1 | | 5x/8=2x/3-1 | | 5x+13=9x-39 | | -7p+3p=8 | | 3lnx=2 | | 7z-8=3z+24 | | -2/5x-1=3 | | 777/6 | | -4(x+5)=3(x-11) | | 2x-0.3-2.6x=3.42 | | 2x*5=11 | | v+5=8 | | 8=-5/6z-12 | | 2-3(3x-4)+5=52 | | -3(x+8)-2(4x-3)=-7 | | -3=5v-5 | | Xlnx=6lnx | | x+3.5=9 | | (4f+5)-(-5f-40)=180 | | -94-x=-12x+49 | | 13x^2-16x=4 | | 4(k+5)=2(9t-2) | | 4(v-8)=-2v-26 | | 8x=-8x-7x | | xsquared+12=1 | | 2x^2=x+29 | | -7(v+4)+5(6-7v)=44 | | 5d+7x+6= | | -36-3x=64-8x | | 12-8-12= | | 5-3x/4=4 |